AN ANALYSIS OF WORKLOAD AND WORK-LIFE BALANCE AMONG NURSES IN GOVERNMENT AND PRIVATE HOSPITALS IN MADURAI DISTRICT - C., Revathi; Hema Malini, A. (ShodhKosh: Journal of Visual and Performing Arts, 2024)
This research article investigates the intricacies of family-work life balance and workload among nurses employed in both government and private hospitals within the Madurai district. The study aims to discern potential disparities between these two sectors and shed light on the challenges nurses face in reconciling their professional responsibilities with their personal lives. Through a rigorous empirical analysis, the study unveils notable variations in work-life balance and workload experienced by nurses in government and private hospital settings. Government hospital nurses are found to contend with higher workloads compared to their counterparts in private hospitals. Factors contributing to this disparity include patient volume, resource constraints, and organizational dynamics inherent in government healthcare institutions.